Policy on Poverty Reduction of Farmers Through Social Capital (Case Study of Farmers in Poor Village Purworejo) - Rinawati, A; ., Rusdarti; Soesilowati, E (KnE Social Sciences, 2018)
The purpose of research to analyze the role of social capital as one policy in alleviating poverty of farmers in Purworejo District. This research is expected to contribute to the policy of poverty alleviation model for poor farmers. The study sites were selected in poor villages in Purworejo District. Furthermore, the method used is descriptive qualitative by using field study method and type of phenomenology research. Data were collected by observation, in-depth interview and FGD. The result of the role of social capital in the form of trust, norms and social networks as a policy to alleviate poverty, especially on farmers in poor villages. The role of norms as a set of rules to maintain the quality of social relationships in the form of social networks at the family, neighboring, farmer groups and institutions. Where this social network will continue to survive if supported by the trust. This research also shows that social capital of trust becomes the main element for farmers in survival. The element of trust is seen when borrowing seeds, fertilizers, medicines, and farming equipment to wetland owners. Utilization of social capital in the form of trust, norms and social networks are used by farmers in both production and consumption activities. Keywords: poverty policy, social capital, poor village,